Покращення якості технології процесу запресовування зубків у шарошки бурових доліт - Сліпчук, Андрій Миколайович; Яким, Роман Степанович (НТУ "ХПІ", 2017)
Аналізом характеру пошкоджень поверхонь отворів виявлені сліди від дії сил стиску що виникають вздовж осі зубка при втисненні його в породу вибою. Також виявлено сліди деформації від дії згину на зубок залежно від орієнтації його ковзання по вибою. Фіксували й притирання, фреттинг-корозію, пошкодження локальних ділянок стінок отворів спричинені прокручуванням зубка навколо своєї осі в отворі вінця шарошки. У випадку застосування зубків із симетричним загостренням породоруйнівної частини ефективним виявляється орієнтація твірної вражаючої головки зубка під деяким кутом до осі вінця шарошки. Розрахунки показують, що оптимальним є такий кут рівний 45°.

The analysis of the nature of the damage to the surfaces of the openings revealed traces of the action of the compressive forces arising along the axis of the tungsten carbide inset cutter when squeezing it into the rock face. Also found traces of deformation from the action of bending to the tungsten carbide inset cutter, depending on the orientation of its slip on the face. Fixing and rubbing, fretting-corrosion, damage to the local areas of the walls of the holes caused by scrolling the tungsten carbide inset cutter around its axis in the opening of the rolling-cutter teeth row. In the case of the use of tungsten carbide inset cutter with symmetrical exacerbation of the breeding part, the orientation of the creature's impressive head of the tungsten carbide inset cutter is determined by an effective angle to the axis of the crown of the tungsten carbide inset cutter pick. Calculations show that an angle of 45° is optimal.
Keywords: оснащення породоруйнівне; навантаження; момент крутний; ковзання; деформація; crimping of teeth; drill bits